MODEL INTEGRATIF KOLABORASI ANTAR ORGANISASI DALAM PENGUATAN KAPASITAS EKONOMI DESA BERBASIS KEMITRAAN PUBLIK - Yusuf Musyaffa; Asyim Burhani; Mulyaningsih Mulyaningsih; Ike Kania (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2026)
This study aims to examine and formulate an integrative model of inter-organizational collaboration in strengthening village economic capacity based on public partnerships. This study focuses on the interaction between PT Permodalan Nasional Madani (PNM), the local government, and the village government as the main actors in local economic development. The approach used was qualitative, with a literature-based conceptual analysis and a theoretical synthesis of the concepts of collaborative governance, inter-organizational collaboration, and public-private partnership. The results indicate that the effectiveness of collaboration is largely determined by factors such as trust, shared vision, facilitative leadership, and institutional capacity. Furthermore, it was found that the integration of roles between actors can increase access to economic resources, strengthen local institutions, and encourage community participation. This study produces an integrative model of collaboration that is adaptive and contextual, and can be used as a framework for strengthening village economic capacity. The contribution of this research lies in the development of a collaborative model based on public partnerships that is relevant in the context of village development in developing countries.